Quality Control Inspection Results Platelets and Leukocytes Based on the Westgard Rule and Six Sigma at Rs Pku Muhammadiyah Bantul - Oktavia Amanda Putri; Woro Umi Ratih; Monika Putri Solikah (Journal of Social Science, 2024)
Internal Quality Consolidation (PMI) is a preventive and monitoring activity carried out by each laboratory continuously so that errors or deviations do not occur so that correct inspection results are obtained, one of which is carrying out quality control (QC) using the Westgard Rule and Six Sigma . The Westgard rule is used to see whether there are analytical errors that occur with the 12 S , 13 S , 22 S , R4 S , 41 S , 10 X series of rules . Six sigma is used to assess the quality of a laboratory's performance by looking at the minimum sigma value level with a value of 3? and a maximum of ?6?. This research aims to evaluate quality control (QC) results including accuracy, precision, Levey-Jennings control charts based on the Westgard rule , as well as six sigma values along with DPMO. The research method used was a quantitative descriptive method using secondary data from the results of examination of platelet and leukocyte control materials in January, February and March 2024. The calculation results from the accuracy (d%) and precision (CV%) values of platelet examination were 5.18% and 3.32%, while the leukocyte examination was -3.08% and 0.97%. Evaluation with the Westgard rule in platelet examination gets the 12s, 13s, 22s and 10x rules, while leukocyte examination gets the 12s and 13s rules. The six sigma and DPMO values for platelet examination were 5.97 and 5.4, 4.26 and 3.467, 4.71 and 687 while leukocyte examination were 18.64 and 0.001, 7.01 and 0.019, 9.6 and 0.001. This research can It was concluded that the examination of platelets and leukocytes had good accuracy and precision, there were control values that followed the Westgard rule , as well as six sigma values ? 3? and DPMO ?66.807.